Mitochondrial Costs of Being Hot: Effects of Acute Thermal Change on Liver Bioenergetics in Toads (Bufo bufo) - Roussel, Damien; Voituron, Yann (Frontiers in Physiology, 2020)
Global climatic warming is predicted to drive extreme thermal events, especially in temperate terrestrial environments. Hence, describing how physiological parameters are affected by acute temperature changes would allow us to understand the energy management of organisms facing such non-predictable and constraining events. As mitochondria play a key role in the conversion of energy from food into ATP but also produce harmful reactive oxygen species (ROS), the understanding of its functioning is crucial to determine proximal causes of potential decline in animal’s performance. Here, we studied the effects of acute temperature changes (between 20°C and 30°C) on mitochondrial respiration, ATP synthesis rate, oxidative phosphorylation efficiency (ATP/O) and H2O2 generation in isolated liver mitochondria of a terrestrial ectotherm, the common toad (Bufo bufo). Using succinate as respiratory substrate, we found that mitochondrial rates of oxygen consumption, ATP synthesis and H2O2 generation increased as temperature increased, being 65%, 52% and 66% higher at 30°C than at 20°C, respectively. We also found that mitochondrial coupling efficiency (ATP/O) decreased while the oxidative cost of ATP production (H2O2/ATP ratio) increased. The present results further indicate that between 40% and 60% of temperature effects on mitochondrial ATP production and H2O2 generation was at minima driven by an action on the oxidative capacity of mitochondria. These results suggest that B. bufo may need to allocate extra energy to maintain ATP production and protect cells from oxidative stress, reducing the energy allocable performances.